THE OLD POLISH LITERATURE WRITTEN BY PROTESTANTS. SELECTED METHODOLOGIES - Chemperek, Dariusz (Prace Polonistyczne, 2021)
The article presents four research methods that find application in the study of literary works written by Polish Protestants in the Old Polish epoch. The first one is a reconstruction of the theological (religious, ethical) programme of the writers who openly declare that they are Evangelicals or Anti-Trinitarians. What serves as a liminal case are funeral works about high-ranking people and addressed to Christians in general – here Protestant writers use the principle of denominational modesty, although in the terms of inventio their rhetoric is different from that of Catholics. The second method consists in examining the religious background of ludic works (e.g. epigrams) from the perspective of cultural hermeneutics – an analysis of symbolism, and historical and moral references. A researcher must go even deeper when analysing parenteral or didactic works addressed to general readers and promoting the Protestant ethos, usually in a subtle and consistent manner. The fourth method is usually used when studying anonymous poems (from the 17th century) or those in which the religious declaration is vague. These texts can be successfully examined using the philological method of tracking phrases from denominational Bibles and songs from popular Protestant hymn-books (“biblical and song pebbles” inlaid into the mosaic of the work). Yet, the researcher also needs to pay attention to subtle theological allusions (sometimes in Aesopian speech) that are characteristic of Protestantism.